Low power flip-flop circuits for high performance systems - Leong, Chooi Sze. (2011)
With the vast advancement in VLSI technology, tens of millions of transistors are integrated on a single chip and the number of transistors will continue to increase in years to come. In line with the increasing demand of portable applications in high speed circuits, power consumption has become one of the main problems in achieving high performance systems. Clocked storage elements such as latch and flip-flop designs have been challenging, to achieve low power design while sustaining high-speed performance and small-area consumption.